Development of an Enzyme-Linked Immunosorbent Assay Based on CD150/SLAM for the Detection of Peste des Petits Ruminant Virus - Prajapati, Meera; Dou, Yongxi; Zhu, Xueliang; Zhao, Shuaiyang; Alfred, Niyokwishimira; Li, Yanmin; Zhang, Zhidong (Frontiers in Veterinary Science, 2020)
Peste des petits ruminant (PPR) is an economically important severe viral disease of small ruminants that affects primarily respiratory and digestive tract. Specific detection of PPR virus (PPRV) antigen plays an important role in the disease control and eradication program. In this study, an indirect enzyme-linked immunosorbent assay based-on recombinant goat SLAM as the capture ligand was successfully developed for the detection of PPRV antigen (PPRV SLAM-iELISA). The assay was highly specific for PPRV with no cross-reactions among foot-and-mouth disease virus, Orf virus, sheep pox and goat pox virus, and a sensitivity with a detection limit of 1.56×101 TCID50/reaction(50µL). Assessment of 136 samples showed that the developed PPRV SLAM-iELISA was well correlated with real-time RT-qPCR assays and commercially available sandwich ELISA for detection of PPRV and showed relative sensitivity and specificity of 94.73% and 100.83% respectively. These results suggest that the developed PPRV SLAM-iELISA is suitable for specific detection of PPRV antigen. This study demonstrated that the recombinant goat SLAM can be used in PPRV diagnostic assay and reports for the first time that the goat SLAM, the cellular receptor for PPRV can be used for the development of diagnostic method.